Strategies of KOMPAQ in Increasing Qur’anic Reading Interest Among Students at Muhammadiyah University of Bengkulu - Lety Febriana; Andi Saputra; Desi Firmasari; Imam Ahmad Amin (Indonesian Journal for Islamic Studies, 2025)
Background of Study: Students’ interest in reading the Qur’an reflects an important dimension of religious character development in higher education. However, many university students demonstrate low consistency and motivation in Qur’anic reading practices.Aims and Scope of the Paper: This study analyzes the strategies employed by the Qur’anic Enthusiast Student Community (KOMPAQ) at Universitas Muhammadiyah Bengkulu in fostering students’ engagement with Qur’anic reading activities.Methods: This research used a descriptive qualitative approach with thematic analysis. Data were collected through in-depth interviews with 8 KOMPAQ core members and 10 active participants, participant observation in mentoring activities, and document analysis of community programs. Data were analyzed using Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing, to identify recurring patterns of strategy implementation.Results: The findings indicate that students’ engagement in Qur’anic reading is influenced by prior educational background and peer environment. KOMPAQ addresses this through several interconnected strategies: (1) creating a psychologically safe and inclusive learning environment; (2) strengthening motivation through peer role models and inspirational member narratives; (3) designing structured yet flexible programs such as halaqah tahsin, tahfizh, One Day One Ayah, One Day One Hadith, and routine tilawah; (4) reinforcing participation through appreciation and symbolic rewards; and (5) utilizing digital platforms and inter-organizational collaboration to expand outreach.Conclusion: These strategies form a thematic pattern of environmental support, motivational reinforcement, program accessibility, and social networking.